Investigations of the generality of quaternary ammonium salts as alkylating agents in direct C–H alkylation reactions: solid alternatives for gaseous olefins. Issue 16 (5th April 2019) - Schönbauer, David; Spettel, Manuel; Pollice, Robert; Pittenauer, Ernst; Schnürch, Michael
Abstract : C–H alkylation reactions using short chain olefins as alkylating agents could be operationally simplified on the lab scale by using quaternary ammonium salts as precursors for these gaseous reagents. Abstract : C–H alkylation reactions using short chain olefins as alkylating agents could be operationally simplified on the lab scale by using quaternary ammonium salts as precursors for these gaseous reagents: Hofmann elimination delivers in situ the desired alkenes with the advantage that the alkene concentration in the liquid phase is high. In case a catalytic system did not tolerate the conditions for Hofmann elimination, a very simple spatial separation of both reactions, Hofmann elimination and direct alkylation, was achieved to circumvent possible side reactions or catalyst deactivation. Additionally, the truly catalytically active species of a rhodium(i ) mediated alkylation reaction could be identified by using this approach.